Chronic prolymphocytoid leukaemia with an unusual immature immunophenotype. Issue 5 (May 1994) - Lima, M; Coutinho, J; Orfão, A; Macedo, A L; San Miguel, J F; Justiça, B
Abstract : A case of a 58 year old woman with a chronic lymphoproliferative disorder of unusual clinical presentation, disease course, and immunophenotype is presented. At diagnosis she had severe anaemia, moderate lymphocytosis with some cells having prolymphocytoid features and a normal platelet count. A clinical examination yielded negative results. Only anaemia related symptoms were found and the patient became blood transfusion dependent. Both the lymphocytosis and the proportion of prolymphocytoid cells rose insidiously and thrombocytopenia developed later during the course of the disease. Three years later, the patient had a white cell count of 269 x 10(9)/l almost exclusively of prolymphocytoid cells and the bone marrow was diffusely infiltrated. She was refractory to chemotherapy and the anaemia did not improve after treatment with cyclosporine. Lymphoid cells were positive for cytoplasmatic CD3, HLA-Dr, CD34, CD38, CD7, CD56, CD13, CD33 and CD65. Membrane alpha beta and gamma delta T cell receptors (TCRs) were not expressed and the beta chain TCR gene was in germline configuration. Other membrane T, B, natural killer, and myelomonocytic markers were negative. Karyotype analysis was tried several times but metaphases were not obtained, even after stimulation with T cell mitogens.